Quality of life of software employees with reference to Kannur, Kerala - ., Sreelal; Godanavalli, G (International Journal of Engineering and Technology, 2018)
Indian Information technology sector is one of the largest sectors which significantly contributes the economy of the country. The problems associated with the nature of job arises the question on the satisfaction of the employees on their life or quality of life. Thus the present study focuses on the quality of life of the software employees and the factors influencing the quality of life of the software employees. The results show that quality of life of the software employees was moderate and demographic variables namely age, gender, place of living, monthly income and years of experience influences the quality of life of the software employees. The suggestion for enhancing the quality of life of the software employees are discussed in the article.Â Â